Unusable Radial Artery for Severe Atherosclerosis in a Young Patient. Issue 3 (15th May 2014) - Settepani, Fabrizio; Cappai, Antioco; Citterio, Enrico; Melis, Licia C.M.; Tarelli, Giuseppe
Abstract We report a young diabetic patient who was found to have an unusable radial artery (RA) for coronary bypass grafting because of severe and diffuse atherosclerosis. Techniques to diagnose RA conduits, which are not usable for coronary surgery, are reviewed. doi: 10.1111/jocs.12356 (J Card Surg 2015;30:263–264)